Single-layer fluorinated MXene / perfluoropolyether composite lubricating oil

By efficiently dispersing the single-layer fluorinated MXene nanofunctional filler Fn-Ti3C2Tx MXene in PFPE, the problem of nanofunctional filler being difficult to disperse and easily agglomerate in PFPE is solved, high dispersion and stability are achieved, and lubrication performance and anti-wear and friction reduction performance are significantly improved. It is suitable for lubrication applications under harsh conditions.

CN119752518APending Publication Date: 2025-04-04SHAANXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411971127.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The nanofunctional filler particles in existing PFPE composite lubricating oil are difficult to disperse and easily agglomerate in PFPE, resulting in poor stability of the lubricating oil and difficult to meet the needs of actual application.

Method used

The single-layer fluorinated MXene nanofunctional filler Fn-Ti3C2Tx MXene is prepared with ultrasonic assistance by using the two-step one-pot method or four-step one-pot method, and its compatibility with PFPE is improved by grafting the perfluorooligomer chain, thereby achieving high dispersion and stability of nanofunctional filler in PFPE.

Benefits of technology

It realizes high dispersion and stability of nanofunctional fillers in PFPE, significantly reduces the friction coefficient, improves the lubricating performance and anti-wear friction reduction performance of composite lubricating oil, and is suitable for lubricating applications under harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752518A_ABST
    Figure CN119752518A_ABST
Patent Text Reader

Abstract

The invention discloses a single-layer fluorinated MXene / perfluoropolyether composite lubricating oil, the composite lubricating oil is prepared by introducing and dispersing a single-layer fluorinated MXene (Fn-Ti3C2Tx MXene) nano functional filler into perfluoropolyether (PFPE) at room temperature, the preparation method is simple and efficient, industrial production is easy, and the composite lubricating oil is excellent in comprehensive performance and wide in application prospect. The lubricating oil is especially suitable for lubrication under harsh conditions and complex working conditions. The added Fn-Ti3C2Tx MXene can be obtained by firstly etching MAX-phase Ti3AlC2 under the assistance of ultrasonic waves to obtain the Ti3C2Tx MXene and then fluorinating and grafting the surface of the Ti3C2Tx by using an acyl fluoride group-terminated perfluorinated oligomer, and the preparation process successfully realizes the coupling and efficient integration of etching and fluorinating grafting. The filler has ideal compatibility and dispersibility in PFPE, and is a key for the Fn-Ti3C2Tx MXene / PFPE composite lubricating oil to have excellent comprehensive properties such as wear resistance and friction reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fluorine-containing functional lubricating materials, and in particular relates to a single-layer fluorinated MXene / perfluoropolyether composite lubricating oil. Background Art

[0002] Perfluoropolyether (PFPE) is a polyether in which all CH bonds on the polymer chain are replaced by CF bonds. Due to the large electronegativity of the F atom (the largest electronegativity among known elements), the high bond energy of the CF bond (the highest bond energy among known single bonds), and the rich conformational isomerism of the COC bonds on the main chain, this unique structure gives PFPE excellent properties, such as low surface tension, low volatility, low glass transition temperature, high chemical inertness, excellent flexibility, excellent radiation resistance and thermal stability, and a wide operating temperature range. It is one of the lubricants with the best comprehensive performance discovered and prepared by humans so far, and is widely used in defense, aerospace, deep-sea exploration, precision machinery, petrochemicals and other fields.

[0003] Practice has shown that adding nano-functional fillers (such as polytetrafluoroethylene particles, graphene oxide, MXene, MoS2, MoO3, etc.) to PFPE lubricants can help further improve its boundary lubrication ability and comprehensive lubrication properties such as wear resistance. Nano-functional fillers (especially two-dimensional nanomaterials) can not only form a protective film at the friction interface, reduce direct contact between mechanical equipment and reduce the friction coefficient, but also use their own small size characteristics to enter the interface scratches to fill and quickly repair scratches, thereby effectively reducing interface wear. Unfortunately, PFPE and nano-functional fillers are not compatible, which thermodynamically causes nano-functional fillers to be difficult to disperse and easy to agglomerate in PFPE. This defect or deficiency not only makes it difficult for the filler to play its due role, but more importantly, it also leads to poor stability of the lubricant and cannot meet the needs of practical applications. Therefore, it is urgent to design and prepare new nano-functional fillers that can be stably dispersed in PFPE and develop new formulas for composite lubricants, which has important theoretical significance and application value for the development and improvement of PFPE-based high-performance composite lubricants.

[0004] MXene is a new type of transition metal carbon / nitride two-dimensional nano-layered material. Compared with graphene oxide and molybdenum-containing materials, it is more suitable for use as a nano-functional filler for lubricating oil for the following reasons: First, MXene has a lower shear modulus and can reduce friction through interlayer slip during friction; second, MXene's excellent thermal conductivity can effectively alleviate the generation of hot spots during friction and the resulting decomposition of PFPE; third, MXene contains elements such as titanium, chromium, and carbon, which are expected to better repair scratches and reduce wear during friction, thereby improving wear resistance. Therefore, MXene (especially its typical representative Ti3C2T xMXene) has attracted attention in the field of composite materials such as lubricants.

[0005] The invention patent with publication number CN114349918A and the literature (Tribology International, 2022, 170, 107500) reported a fluorinated polymer modified Ti3C2T x The MXene lubricant additive and its preparation method and application are characterized by adopting the following four steps: (1) etching the Ti3AlC2 precursor for 24 to 48 hours using the LiF+HCl method currently used in most literatures, centrifuging the mixed solution multiple times, and freeze-drying the supernatant to obtain Ti3C2T x MXene powder. (2) Ti3C2T x After alkalization treatment for 4 to 24 h, the MXene powder was condensed and coupled with the siloxane end of 3-(trimethoxysilyl)propyl methacrylate (MPS) in ethanol for 4 to 48 h to obtain MPS-modified Ti3C2T with polymerizable methacrylate end groups on the surface. x (3) Under inert atmosphere, 2-(perfluorooctyl)ethyl methacrylate (PFMA) was used as a monomer and reacted with MPS-modified Ti3C2T2 in acetonitrile under the initiation of 2,2-azobisisobutyronitrile. x MXene free radical copolymerization for 4 to 48 h to obtain fluorinated polymer-modified Ti3C2T x MXene lubricant additive. (4) The obtained additive is added to PFPE to prepare fluoropolymer-modified Ti3C2T x The lubrication performance of MXene-modified PFPE composite lubricant was tested and compared with PFPE and other materials. It was found that the addition of additives improved the lubrication performance of the modified PFPE composite lubricant. The main disadvantages or shortcomings of this method are: first, the preparation process is time-consuming (4 to 7 days), the process is complex, the yield is low, and the efficiency is low. Second, MPS-modified Ti3C2T x The surface free radical copolymerization between Ti3C2T and PFMA is heterogeneous, and the limited mass transfer leads to limited degree of copolymerization, poor controllability and repeatability. x MXene is mainly a multilayer structure. After condensation with MPS and copolymerization with PFMA, the particles of the additives are relatively large. In addition, the compatibility of fluoroalkyl methacrylate polymers with PFPE is poor, resulting in the prepared fluorinated polymer modified Ti3C2T x The improvement in the dispersion performance of MXene additives in PFPE is limited, and the stability of the composite lubricant is poor, making it difficult to meet the needs of long-term storage, transportation and application.

[0006] The invention patent with publication number CN115521817A discloses a lubricating oil anti-wear additive and its preparation method and application, which adopts the following four steps: (1) using tetrafluoroethylene and oxygen as raw materials, photopolymerization reaction is carried out at -90 to -30°C under ultraviolet light to obtain PFPE with terminal acyl fluoride. (2) the product stream obtained in step 1 is subjected to reduced pressure distillation at 5000±500Pa and 150 to 200°C, and then hydrolyzed under sulfuric acid catalysis to obtain PFPE with terminal carboxyl. (3) the product obtained in step 2 is reacted with a dibasic organic amine at 100 to 200°C to obtain PFPE with terminal amino. (4) an aqueous solution of molybdenum trioxide in ammonia is mixed with the obtained PFPE with terminal amino under stirring conditions, reacted at 140°C for 5h, and the organic solvent is removed by reduced pressure distillation to obtain a lubricating oil additive. The lubricating oil additive is added to PFPE lubricating oil to improve the lubrication performance of the PFPE composite lubricating oil. However, this method has the following disadvantages or shortcomings: First, the preparation process is time-consuming and complex, especially requiring high temperature, low temperature and ultraviolet light conditions. Secondly, the rich groups on the surface of molybdenum trioxide treated with ammonia water will cause or even aggravate the agglomeration of the molybdenum trioxide particles themselves. During the reaction of molybdenum trioxide particles with different agglomeration degrees with PFPE with amino groups at the end, it is difficult to fully graft and highly disperse molybdenum trioxide. When the obtained additive is added to PFPE lubricant, the overly large molybdenum trioxide particles will become stress concentration areas during the lubrication process, and a good lubrication effect cannot be achieved, which makes it difficult to meet the needs of practical applications.

[0007] Perfluoro oligomers can be regarded as structural fragments or short chains of long-chain PFPE in terms of segment composition and structure. Literature (Macromolecules, 2012, 45, 4907) shows that perfluoro oligomers can be prepared by catalytic anionic ring-opening polymerization of hexafluoropropylene oxide (HFPO), which is low in cost, high in efficiency and good in selectivity. Importantly, the perfluoropropylene oxide oligomers prepared by anionic ring-opening polymerization of HFPO have an end group of acyl fluoride groups COF with high reactivity. Acyl fluoride groups can react quickly and efficiently with functional groups such as hydroxyl and epoxy groups under mild conditions, and perfluoropropylene oxide oligomer chains are efficiently grafted and directed into target molecules, which is of great significance for the design, efficient and controllable preparation and surface functionalization modification of fluorine-containing functional materials such as nano-functional fillers. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the existing PFPE composite lubricant, such as the difficulty in dispersion, easy (re)agglomeration and poor stability of the nano-functional filler particles in the PFPE lubricant, and to provide a single-layer fluorinated MXene / PFPE (F) having excellent stability (the nano-functional filler particles are highly dispersed and not easy to re-agglomerate during storage and use) and excellent anti-wear and friction reduction properties.n -Ti3C2T x MXene / PFPE) composite lubricant.

[0009] The F provided by the present invention n -Ti3C2T x MXene / PFPE composite lubricant is a composite lubricant made by adding nano-functional filler F to PFPE. n -Ti3C2T x MXene powder, the weight percentage composition is: PFPE 98.00% ~ 99.75%, F n -Ti3C2T x MXene 0.25%~2.00%.

[0010] More preferably, the above F n -Ti3C2T x The weight percentage composition of MXene / PFPE composite lubricant is: PFPE 99.00% to 99.50%, F n -Ti3C2T x MXene 0.50%~1.00%.

[0011] The above-mentioned nano-functional filler F n -Ti3C2T x Mxene can be etched with hydrofluoric acid, perfluoropropionic anhydride or perfluoro oligomer (abbreviated as (HFPO) n COF) as the fluorination (grafting) agent in a two-step one-pot preparation (method 1), or by first adding (HFPO) n -COF is hydrolyzed with water to generate hydrofluoric acid in situ as an etchant, and (HFPO) is added later n -COF is a four-step one-pot preparation of a fluorination (grafting) agent (Method 2). The specific preparation method is as follows:

[0012] Method 1: Two-step one-pot method

[0013] Ti3AlC2, HF aqueous solution, perfluoropropionic anhydride or (HFPO) n -COF reacts for 4 to 8 hours under ultrasound assistance, allowing HF to etch Ti3AlC2. During the etching process, perfluoropropionic anhydride or (HFPO) with active reaction end groups n -COF and Ti3C2T generated after etching x The surface hydroxyl groups of MXene reacted, and the reaction mixture was centrifuged, and the obtained solid was washed with deionized water and fully dried to obtain the target nano-functional filler F. n -Ti3C2T x MXene powder.

[0014] Method 2: Four-step one-pot method

[0015] Ti3AlC2, water, etching amount (HFPO) n -COF reacts for 7 to 15 minutes under ultrasound assistance to make (HFPO) n -COF reacts with water to generate HF in situ and etches Ti3AlC2. Etching generates (multi-layer) Ti3C2T x After MXene, the grafting amount of (HFPO) is added under the assistance of ultrasound. n -COF continued to react for 3 to 4 hours, and the added (HFPO) n -COF and Ti3C2T generated after etching x The surface hydroxyl group (grafting) reaction of MXene. After the obtained mixed solution is centrifuged, the solid phase is washed with deionized water and fully dried to obtain the target nano-functional filler F n -Ti3C2T x MXene powder.

[0016] Above (HFPO) n The structural formula of -COF is Here, n is an integer of 2-15, and preferably n is an integer of 2-10.

[0017] Further preferably, in the above method 1, Ti3AlC2, HF aqueous solution, perfluoropropionic anhydride or (HFPO) n -COF was reacted at 20-40°C for 4-8h under ultrasound assistance.

[0018] Further preferably, in the above method 1, the Ti3AlC2, HF aqueous solution, perfluoropropionic anhydride or (HFPO) n The dosage ratio of -COF is 0.50~1.00g:10~20mL:130~260mL.

[0019] More preferably, the mass fraction of HF in the HF aqueous solution is 30% to 50%.

[0020] Further preferably, in the above method 2, Ti3AlC2, water, etching amount (HFPO) n -COF reacts at 20-40℃ for 7-15min under ultrasound assistance, and then adds the grafting amount of (HFPO) n -COF, continue the reaction at 20-40°C for 3-4h.

[0021] Further preferably, in the above method 2, the Ti3AlC2, water, and etching amount of (HFPO) n-COF usage ratio 0.50~1.00g:5~10mL:20~50mL.

[0022] Further preferably, in the above method 2, the Ti3AlC2 and the grafting amount of (HFPO) n -COF usage ratio 0.50~1.00g:40~100mL.

[0023] More preferably, in the above method 1 and method 2, the temperature of the ultrasound is 20-40°C and the power is 100-750W.

[0024] The beneficial effects of the present invention are as follows:

[0025] 1. F of the present invention n -Ti3C2T x MXene / PFPE composite lubricant is prepared by combining a novel single-layer fluorinated MXene nano-functional filler F n -Ti3C2T x MXene is introduced and dispersed in PFPE at room temperature. The preparation method is simple and efficient, the composite lubricant has excellent stability, and has broad application prospects. In particular, compared with PFPE, a small amount of nano-functional filler added (no more than 2wt%) can significantly reduce the friction coefficient and improve the lubrication performance of the composite lubricant.

[0026] 2. F of the present invention n -Ti3C2T x The key or fundamental to the excellent comprehensive performance of MXene / PFPE composite lubricants lies in the addition of nano-functional fillers F with unique structures. n -Ti3C2T x MXene. F n -Ti3C2T x MXene is a single-layer structure. x The MXene surface is grafted with perfluorinated oligomer chains. The outstanding advantages of this structure are as follows: First, since the perfluorinated oligomer chain is just a short chain or structural fragment of PFPE, the short chain itself can be ideally miscible with PFPE, making the Ti3C2T grafted with perfluorinated oligomer chains x MXene (also known as nano-functional filler F n -Ti3C2T x Second, and more importantly, previous literature (Green Chemistry, 2015, 17, 4489-4498) proved that there is a unique and effective F repulsion between the perfluorinated oligomer chains grafted on the surface of the nano-functional filler, which fundamentally prevents the F dispersed in PFPE from the perspective of thermodynamics. n-Ti3C2T x The reagglomeration of MXene and the resulting sedimentation eventually lead to the formation of nano-functional filler F n -Ti3C2T x MXene has ideal dispersion in PFPE and shows no sedimentation or stratification after standing for 2 months.

[0027] 3. The monolayer fluorinated MXene functional nanofiller F introduced in the present invention n -Ti3C2T x MXene is prepared by a two-step one-pot method or a four-step one-pot method under the assistance of ultrasound, which successfully realizes the coupling and efficient integration of the etching and grafting of precursors (such as Ti3AlC2, etc.), with mild conditions, high raw material utilization, and high functional filler yield. Compared with other etching process methods reported in the literature, the method of the present invention reduces the etching reaction time from more than 24 hours to less than 4 hours, and the preparation efficiency is significantly improved. Part of the reason is (HFPO) n -COF has a highly active acyl fluoride group (-COF) at the end, which can quickly and thoroughly react with Ti3C2T x The hydroxyl reaction on the MXene surface achieves efficient grafting to generate the target nano-functional filler F n -Ti3C2T x MXene.

[0028] 4. F provided by the present invention n -Ti3C2T x The preparation method of MXene / PFPE composite lubricant is simple, efficient, easy to industrially produce, store, transport and use, with excellent comprehensive performance. It is especially suitable for lubrication under harsh conditions and complex working conditions. It has important application value in national defense, deep-sea exploration, aerospace, precision machinery, semiconductor manufacturing, petrochemical and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is the single-layer fluorinated MXene nano-functional filler F2-Ti3C2T in Example 1 x Schematic diagram of the structure of MXene.

[0030] Figure 2 The precursors Ti3AlC2 and F2-Ti3C2T in Example 1 x X-ray diffraction spectrum of MXene.

[0031] Figure 3 The precursors Ti3AlC2 and F2-Ti3C2T in Example 1 x X-ray photoelectron spectrum of MXene.

[0032] Figure 4 It is F2-Ti3C2T in Example 1 x Atomic force microscopy image of MXene.

[0033] Figure 5 It is the single-layer fluorinated MXene nano-functional filler F3-Ti3C2T in Example 2 x X-ray diffraction spectrum of MXene.

[0034] Figure 6 The precursors Ti3AlC2 and F3-Ti3C2T in Example 2 x X-ray photoelectron spectrum of MXene.

[0035] Figure 7 The precursors Ti3AlC2 and F3-Ti3C2T in Example 2 x Atomic force microscope image of MXene.

[0036] Figure 8 Ti3C2T x MXene and F2-Ti3C2T in Example 1 x Comparison of the dispersion stability of MXene in PFPE.

[0037] Fig. 9 PFPE, Ti3C2T x MXene / PFPE composite lubricant and 0.75F2-Ti3C2T in Example 1 x Comparison of the friction coefficient of MXene / PFPE composite lubricant versus sliding time.

[0038] Fig.10 PFPE, Ti3C2T x MXene / PFPE composite lubricant and 1.50F2-Ti3C2T in Example 6 x Comparison of the friction coefficient of MXene / PFPE composite lubricant versus sliding time. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0040] Example 1

[0041] 1. Preparation of F2-Ti3C2T x MXene

[0042] Preparation of F2-Ti3C2T by a two-step one-pot method xAt room temperature, 0.5 g Ti3AlC2, 10 mL of 49.9% HF aqueous solution, and 130 mL of hexafluoropropylene oxide dimer containing acyl fluoride end groups (F[CF(CF3)CF2O]CF(CF3)COF, provided by Zhejiang Huanxin Fluoro Materials Co., Ltd.) were added to a polytetrafluoroethylene beaker, and reacted at room temperature for 5 h under 750 W ultrasonic assistance. The reaction mixture was centrifuged and the obtained solid was washed with deionized water until it was nearly neutral, and then dried at 60 ° C for 12 h to obtain a single layer of fluorinated Ti3C2T x MXene, denoted as F2-Ti3C2T x MXene, its structural diagram is as follows Figure 1 As shown (R f Represents F[CF(CF3)CF2O]CF(CF3)-).

[0043] X-ray diffraction, atomic force microscopy and X-ray photoelectron spectroscopy were used to characterize the Ti3AlC2 and F2-Ti3C2T x MXene, see the results Figures 2 to 4 . Figure 2 The X-ray diffraction spectrum results show that after the precursor Ti3AlC2 is etched and grafted, the main peak of the Ti3AlC2 phase at 2θ=39.2° disappears, and the peak at 2θ=9.7° shifts left to 2θ=8.6°, indicating that the interlayer spacing of MXene increases after the Al element is completely etched and grafted. Figure 3 In the X-ray photoelectron spectroscopy, F2-Ti3C2T x MXene has a characteristic peak of F1s at 688.0eV, indicating that the perfluoropolyether chain F[CF(CF3)CF2O]CF(CF3)C(O)- of hexafluoropropylene oxide dimer has been successfully grafted on the MXene surface. At the same time, the disappearance of the original Ti3AlC2 peak corresponding to Al 2p at 71.4eV confirms Figure 1 In the X-ray diffraction, the Al in the precursor Ti3AlC2 was completely etched. In addition, atomic force microscopy was used to prove that the nano-functional filler F2-Ti3C2T x MXene is a single-layer structure (see Figure 4 ). The above results prove that F2-Ti3C2T x MXene was successfully prepared.

[0044] 2. Preparation of F2-Ti3C2T x MXene / PFPE composite lubricant

[0045] 0.0075g F2-Ti3C2T xMXene was added to 0.9925 g of PFPE with a viscosity of 475 cP and dispersed at room temperature for 30 min with an ultrasonic power of 100 W to obtain F2-Ti3C2T x MXene / PFPE composite lubricant, denoted as 0.75F2-Ti3C2T x MXene / PFPE.

[0046] Example 2

[0047] 1. Preparation of F3-Ti3C2T x MXene

[0048] Preparation of F3-Ti3C2T by a four-step one-pot method x MXene. At room temperature, 0.5 g Ti3AlC2, 5 mL water and 37 mL hexafluoropropylene oxide trimer containing acyl fluoride end groups (F[CF(CF3)CF2O]2CF(CF3)COF, provided by Zhejiang Huanxin Fluoro Materials Co., Ltd.) were added to a polytetrafluoroethylene beaker. After reacting at room temperature for 10 min with 750 W ultrasonic assistance, 50 mL hexafluoropropylene oxide trimer containing acyl fluoride end groups was added again, and the reaction was continued at room temperature for 4 h with 400 W ultrasonic assistance. After the reaction was completed, the reaction mixture was centrifuged and the obtained solid was washed with deionized water until it was nearly neutral, and then dried at 60 ° C for 12 h to obtain a single layer of fluorinated Ti3C2T x MXene, denoted as F3-Ti3C2T x MXene. Figures 5 to 7 Visible F3-Ti3C2T x MXene was successfully prepared.

[0049] 2. Preparation of F3-Ti3C2T x MXene / PFPE composite lubricant

[0050] 0.0075g F3-Ti3C2T x MXene was added to 0.9925 g of PFPE with a viscosity of 475 cP and dispersed at room temperature for 30 min with the assistance of ultrasound at a power of 150 W to obtain F3-Ti3C2T x MXene / PFPE composite lubricant, denoted as 0.75F3-Ti3C2T x MXene / PFPE.

[0051] Example 3

[0052] 1. Preparation of F4-Ti3C2T x MXene

[0053] Preparation of F4-Ti3C2T by a four-step one-pot methodx MXene. At room temperature, 0.5 g Ti3AlC2, 5 mL water and 49 mL hexafluoropropylene oxide tetramer containing acyl fluoride end groups (F[CF(CF3)CF2O]3CF(CF3)COF, provided by Zhejiang Huanxin Fluoro Materials Co., Ltd.) were added to a polytetrafluoroethylene beaker. After reacting for 10 minutes at room temperature with 700 W ultrasonic assistance, 60 mL hexafluoropropylene oxide tetramer containing acyl fluoride end groups was added again, and the reaction was continued for 4 hours at room temperature with 600 W ultrasonic assistance. After the reaction was completed, the reaction mixture was centrifuged and the obtained solid was washed with deionized water until it was nearly neutral, and then dried at 60 ° C for 12 hours to obtain a single layer of fluorinated Ti3C2T x MXene, denoted as F4-Ti3C2T x MXene.

[0054] 2. Preparation of F4-Ti3C2T x MXene / PFPE composite lubricant

[0055] 0.0075g F4-Ti3C2T x MXene was added to 0.9925 g of PFPE with a viscosity of 650 cP and dispersed at room temperature for 30 min with the assistance of ultrasound at a power of 200 W to obtain F4-Ti3C2T x MXene / PFPE composite lubricant, denoted as 0.75F4-Ti3C2T x MXene / PFPE.

[0056] Example 4

[0057] 1. Preparation of F1-Ti3C2T x MXene

[0058] Preparation of F1-Ti3C2T by a two-step one-pot method x MXene. At room temperature, 0.5 g Ti3AlC2, 10 mL of 49.9% HF aqueous solution, and 130 mL of perfluoropropionic anhydride (CF3CF2COOCOCF2CF3, provided by Sinopharm Chemical Reagent Co., Ltd.) were added to a polytetrafluoroethylene beaker, and reacted at room temperature for 5 h with 550 W ultrasonic assistance. The reaction mixture was centrifuged, and the obtained solid was washed with deionized water until it was nearly neutral, and then dried at 60 ° C for 12 h to obtain a single layer of fluorinated Ti3C2T x MXene, denoted as F1-Ti3C2T x MXene.

[0059] 2. Preparation of F1-Ti3C2T x MXene / PFPE composite lubricant

[0060] 0.0200g F1-Ti3C2T x MXene was added to 0.9800 g of PFPE with a viscosity of 300 cP and dispersed at room temperature for 30 min under the assisted ultrasound of 100 W to obtain F1-Ti3C2T x MXene / PFPE composite lubricant, denoted as 2.00F1-Ti3C2T x MXene / PFPE.

[0061] Example 5

[0062] 1. Preparation of F 15 -Ti3C2T x MXene

[0063] A two-step one-pot method was used to prepare F 15 -Ti3C2T x At room temperature, 0.5 g Ti3AlC2, 10 mL 49.9% HF aqueous solution, and 130 mL tetradecamer of hexafluoropropylene oxide (F[CF(CF3)CF2O] 14 CF (CF3)COF, provided by Zhejiang Huanxin Fluoro Materials Co., Ltd.) was added to a polytetrafluoroethylene beaker and reacted at room temperature for 5 h under 600W ultrasonic assistance. The reaction mixture was centrifuged and the obtained solid was washed with deionized water until it was nearly neutral and dried at 60 °C for 12 h to obtain a single layer of fluorinated Ti3C2T x MXene, denoted as F 15 -Ti3C2T x MXene.

[0064] 2. Preparation of F 15 -Ti3C2T x MXene / PFPE composite lubricant

[0065] 0.0025g F 15 -Ti3C2T x MXene was added to 0.9975 g of PFPE with a viscosity of 1200 cP and dispersed at room temperature for 30 min with the assistance of ultrasound at a power of 250 W to obtain PFPE. 15 -Ti3C2T x MXene / PFPE composite lubricant, denoted as 0.25F 15 -Ti3C2T x MXene / PFPE.

[0066] Example 6

[0067] 1. Preparation of F2-Ti3C2Tx MXene

[0068] Prepare F2-Ti3C2T according to the method of step 1 of Example 1 x MXene.

[0069] 2. Preparation of F2-Ti3C2T x MXene / PFPE composite lubricant

[0070] 0.0150g F2-Ti3C2T x MXene was added to 0.9850 g of PFPE with a viscosity of 475 cP and dispersed at room temperature for 30 min with an ultrasonic assisted power of 120 W to obtain F2-Ti3C2T x MXene / PFPE composite lubricant, denoted as 1.50F2-Ti3C2T x MXene / PFPE.

[0071] Example 7

[0072] 1. Preparation of F3-Ti3C2T x MXene

[0073] Prepare F3-Ti3C2T according to the method of step 1 of Example 2 x MXene.

[0074] 2. Preparation of F3-Ti3C2T x MXene / PFPE composite lubricant

[0075] 0.0100g F3-Ti3C2T x MXene was added to 0.9900 g of PFPE with a viscosity of 750 cP and dispersed at room temperature for 30 min with the assistance of ultrasound at a power of 200 W to obtain F3-Ti3C2T x MXene / PFPE composite lubricant, denoted as 1.00F3-Ti3C2T x MXene / PFPE.

[0076] Example 8

[0077] 1. Preparation of F4-Ti3C2T x MXene

[0078] Prepare F4-Ti3C2T according to the method of step 1 of Example 3 x MXene.

[0079] 2. Preparation of F4-Ti3C2T x MXene / PFPE composite lubricant

[0080] 0.0100g F4Ti3C2T x MXene was added to 0.9900 g of PFPE with a viscosity of 400 cP and dispersed at room temperature for 30 min with the assistance of ultrasound at a power of 200 W to obtain F4-Ti3C2T x MXene / PFPE composite lubricant, denoted as 1.00F4-Ti3C2T x MXene / PFPE.

[0081] The dispersibility of fillers in PFPE will significantly affect the lubrication performance of the corresponding composite lubricant. x The dispersibility of Mxene in PFPE was evaluated, and Ti3C2T x MXene (6 g LiF and 30 mL 12 M HCl aqueous solution were added to a polytetrafluoroethylene beaker, and then 0.5 g Ti3AlC2 was added, and the mixture was reacted at 40 °C for 24 h, centrifuged and washed with deionized water until it was nearly neutral, and the supernatant was freeze-dried to obtain Ti3C2T x The dispersion of MXene in PFPE was compared with the results shown in Figure 8 .Depend on Figure 8 It can be seen that Ti3C2T x After being dispersed in PFPE, Mxene settled significantly within less than 3 days of standing, while F2-Ti3C2T x After MXene was dispersed in PFPE and left to stand for 2 months, no sedimentation was observed, proving that the nano-functional filler F2-Ti3C2T x MXene can maintain an ideal high dispersion state in PFPE for a long time, which further explains that F2-Ti3C2T x MXene / PFPE composite lubricant has excellent stability.

[0082] In order to further demonstrate the beneficial effects of the present invention, a Bruker UMT-2 friction and wear tester was used to test the 0.75F2-Ti3C2T x MXene / PFPE and 1.50F2-Ti3C2T prepared in Example 6 x The tribological properties of MXene / PFPE were tested and evaluated under the following conditions: the load was 60N, the test time was 30min, and the contact form of the friction pair was point-to-surface contact in the ball-disk mode. x MXene (prepared as above) PFPE (same as in Example 1) composite lubricant (denoted as Ti3C2T xThe tribological properties of MXene / PFPE) were compared, and the results are shown in Fig. 9 and Fig.10 . Fig. 9 and Fig.10 It shows that compared with PFPE and Ti3C2T x MXene / PFPE, 0.75F2-Ti3C2T x MXene / PFP E and 1.50F2-Ti3C2T x The friction coefficient of MXene / PFPE is significantly reduced, proving that the single-layer nano-functional filler F2-Ti3C2T x The introduction of MXene significantly reduces the friction coefficient of the composite lubricant, thereby significantly improving its friction performance.

Claims

1. A single-layer fluorinated MXene / perfluoropolyether composite lubricant, characterized in that: The composite lubricant is composed of 98.00% to 99.75% perfluoropolyether and 0.25% to 2.00% monolayer fluorinated MXene by weight percentage; The above-mentioned single-layer fluorinated MXene is prepared by any one of the following methods: Method 1: Ti3AlC2, HF aqueous solution, perfluoropropionic anhydride or perfluoro oligomer are reacted under ultrasound assistance for 4 to 8 hours. After the reaction mixture is centrifuged, the obtained solid phase is washed with deionized water and fully dried to obtain a monolayer fluorinated MXene; Method 2: Ti3AlC2, water, and etching amount of perfluoro oligomer are reacted under ultrasound assistance for 7 to 15 minutes, and then the grafting amount of perfluoro oligomer is added and the reaction is continued for 3 to 4 hours. After the reaction mixture is centrifuged, the solid phase is washed with deionized water and fully dried to obtain a single-layer fluorinated MXene; The structural formula of the above perfluoro oligomer is Wherein n is an integer from 2 to 15.

2. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 1, characterized in that: The weight percentage composition of the composite lubricant is: 99.00% to 99.50% of perfluoropolyether and 0.50% to 1.00% of single-layer fluorinated MXene.

3. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 1, characterized in that: In the method 1, Ti3AlC2, HF aqueous solution, perfluoropropionic anhydride or perfluoro oligomer are reacted at 20-40°C for 4-8 hours under the assistance of ultrasound.

4. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 3, characterized in that: In the method 1, the usage ratio of Ti3AlC2, HF aqueous solution, and perfluoropropionic anhydride or perfluoro oligomer is 0.50-1.00 g: 10-20 mL: 130-260 mL.

5. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 3 or 4, characterized in that: The mass fraction of HF in the HF aqueous solution is 30% to 50%.

6. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 1, characterized in that: In the second method, Ti3AlC2, water, and an etching amount of perfluoro oligomer are reacted at 20-40°C for 7-15 minutes under the assistance of ultrasound, and then a grafting amount of perfluoro oligomer is added and the reaction is continued at 20-40°C for 3-4 hours.

7. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 6, characterized in that: In the second method, the usage ratio of Ti3AlC2, water and the perfluoro oligomer used for etching is 0.50-1.00 g: 5-10 mL: 20-50 mL.

8. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 6, characterized in that: In the second method, the ratio of Ti3AlC2 to the grafting amount of perfluoro oligomer is 0.50-1.00 g:40-100 mL.

9. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 3 or 6, characterized in that: The temperature of the ultrasound is 20-40°C and the power is 100-750W.

10. The single-layer fluorinated MXene / perfluoropolyether composite lubricant according to claim 1, characterized in that: In the structural formula of the perfluoro oligomer, n is an integer of 2 to 10.

Citation Information

Patent Citations

  • Fluorine-containing polymer modified Ti3C2Tx MXene lubricating oil additive as well as preparation method and application thereof

    CN114349918A

  • Lubricating oil anti-wear additive as well as preparation method and application thereof

    CN115521817A